Seasonal Influenza Vaccine Intention among Nurses Who Have Been Fully Vaccinated against COVID-19: Evidence from Greece - Petros Galanis; Aglaia Katsiroumpa; Irene Vraka; Olga Siskou; Olympia Konstantakopoulou; Theodoros Katsoulas; Daphne Kaitelidou (Vaccines, 2023)
Seasonal influenza continues to be a significant public health issue causing hundreds of thousands of deaths annually. Nurses are a priority risk group for influenza vaccination and a high vaccine uptake rate among them is crucial to protect public health. Thus, the aim of our study was to estimate the levels of influenza vaccine acceptance, as well as its determinants, among nurses for the 2022/2023 season. We conducted a cross-sectional study with a convenience sample in Greece. We collected data via an online survey in September 2022. Most of the nurses in the study possessed a MSc/PhD diploma (56.2%) and had previously been infected by SARS-CoV-2 (70.3%). Among nurses, 57.3% were willing to accept the influenza vaccine, 19% were hesitant, and 23.7% were unwilling. Older age, higher levels of perceived support from significant others, and higher COVID-19-related physical exhaustion were positively related to influenza vaccination intention. In contrast, more side effects because of COVID-19 vaccination and higher levels of exhaustion due to measures taken against COVID-19 were negatively associated with vaccination intention. Since the influenza vaccination acceptance rate among nurses was moderate, policymakers should develop and implement measures tailored specifically to nurses in the context of the COVID-19 pandemic to decrease vaccine hesitancy.